Metastasis-Associated Protein 1 Is Involved in Angiogenesis after Transarterial Chemoembolization Treatment. (15th May 2017) - Xue, Tao; Feng, Wenming; Yu, Hongbin; Zhu, Ming; Fei, Maoyun; Bao, Ying; Wang, Xiaoyi; Ma, Wenxue; Lv, Guiyuan; Guan, Jianming; Chen, Suhong
Abstract : Background. Transarterial chemoembolization (TACE), a well-established treatment for unresectable hepatocellular carcinoma (HCC), blocks the arterial blood supply to the tumor, which can be short-lived as development of collateral neovessels, leading to the failure of treatment. Metastasis-associated protein 1 (MTA1) is involved in development of tumors and metastases. However, the role of MTA1 in angiogenesis is still obscure. Methods. We detected the expression of MTA1 and hypoxia-inducible factor-1 α (HIF-1 α ) and microvessel density (MVD) value in liver tumor tissues and tumor periphery before and after TACE treatment. Hepatocellular carcinoma cell line HepG2, tube formation assay, and chorioallantoic membrane (CAM) assay were applied to explore the mechanism of MTA1 in angiogenesis. Results. We found that expression of MTA1 increased after TACE treatment, especially in tumor periphery, which was accompanied by markedly elevated MVD value, indicating a significant correlation between MTA1 and MVD value. Moreover, MTA1 contributed to neovascularization of residual tumors. Cellular experiments further revealed that MTA1 increased the stability and the expression of HIF-1 α, and overexpression of MTA1 enhanced tube formation and neovessels of chick embryos. Conclusions. MTA1 is an active angiogenic regulator; our results shed light on better understanding in neovascularization, which are helpful to predict prognosis of TACE, and provide evidences for intervention to improve therapeutic effects on HCC.